DEVELOPMENT STRATEGY OF THE FACILITY TRADITIONAL FISH LANDING SITES (MEDIATOR) IN THE VILLAGE OF WEST BAGAN, BANGKO SUBDISTRICT, ROKAN HILIR, RIAU PROVINCE - Yaumil Atia; Jonny Zain; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Abstract: Village of West Bagan is a village with a population of the second largest fishermen in the district of Bangko, RokanHilir, Riau Province. Fishermen of the West Bagan village, land and sell their catch in private mediators. However, the facilities available are not enough to meet the needs of fishing supplies consisting of fuel, fresh water and ice. Therefore, this research with survey method was undertaken to obtain the development strategy of the facility by using SWOT analysis. From 9 units mediator were still active, taken 3 units mediator as representatives of large, medium, and small category namely are consecutevely Jumadi mediator, Lausi mediator, dan Asmara mediator. Based on SWOT analysis has been done on each of the mediators obtained one most likely to be develop is mediator Jumadi. In the diagram strategy, mediator Jumadi located in quadrant I with the highest coordinate value, which is a provitable situation. Recommendations strategyis progressive, which means the mediator has the opportunity and the power that can take advantage of existing opportunities. The strategy applied in this condition is to support aggressive growth policy.Keywords: Strategy, Develop, Traditional Fish Landing Sites